Revista parque geológico do varvito: edição comemorativa pelos 20 anos de fundação do parque - Furlan, Lucas Moreira [UNESP]; Pelisam, Luis Gustavo Trettel [UNESP]; Florencio, Gabriela Marques [UNESP]; Farias, Vanderlei de [UNESP]; Biquinhão, Fernanda Fonseca Polessa [UNESP]; Leite Júnior, Washington Barbosa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Located in the county of Itu (SP), the Varvite Geological Park completed, on 23 July 2015, 20 years of foundation. For allowing the study and appreciation of sedimentary rocks known as varvites of glacial origin of the Permo-Carboniferous Period, is one of the greatest geological treasures of the country, so it's constant attention target by the management team of the municipality of Itu and scholars from various fields. Thus, an agreement between the Universidade Estadual Paulista "Julio de Mesquita Filho" and the management team of the municipality of Itu was signed, aiming at the constant revitalization of the park, spreading the importance and geological knowledge that the site provides to visitors and scholars, as well as training with teachers of the municipal school system and local tour guides. Students of the Tutorial Education Program (PET) of the Geology degree of Rio Claro, took over the production of a commemorative magazine for 20 years of the Park Foundation, which in partnership with the Department of Environment of Itu , rescued the history of local time when the rock varvite was still exploited until this day. Guided by teachers of the Institute of Geosciences and Exact Sciences, students also prepared texts explaining all the geological processes that occurred about 280 million years ago and that gave rise to rocks found in the park.

Localizado na Estância Turística de Itu (SP), o Parque Geológico do Varvito completou, no dia 23 de julho de 2015, 20 anos de fundação. Por permitir o estudo e apreciação de rochas sedimentares conhecidas como Varvitos ou ritmitos várvicos, de origem glacial do Período Permo-Carbonífero, é um dos maiores tesouros geológicos do país, por isso, é alvo de constante atenção por parte da equipe administrativa do município de Itu e de estudiosos de diversas áreas. Deste modo, um convênio entre a Universidade Estadual Paulista "Júlio de Mesquita Filho" e a Prefeitura da Estância Turística de Itu foi firmado, tendo como objetivo a constante revitalização do Parque, divulgação da importância e do conhecimento geológico que o local proporciona a visitantes e estudiosos, além de capacitações com professores da rede de ensino municipal e guias turísticos locais. Os alunos do Programa de Educação Tutorial (PET) do curso de Geologia do campus de Rio Claro, assumiram a confecção de uma revista comemorativa pelos 20 anos de fundação do Parque, onde em parceria com a Secretaria de Meio Ambiente de Itu, resgataram a história do local desde período em que a rocha varvito ainda era explorada até os dias atuais. Orientados por professores do Instituto de Geociências e Ciências Exatas, os alunos também elaboraram textos explicando todos os processos geológicos que ocorreram há aproximadamente 280 milhões de anos e que originaram as rochas encontradas no parque.
Keywords: Varvite Geological Park; Tourism Itu; Commemorative magazine; Parque Geológico do Varvito; Estância turística de Itu; Revista comemorativa